Fabrication of electrocatalyst based on PEDOT-PSS supported Pd nanoparticles for ethanolic electro-oxidation - Climaco, Maria Ivona F.; Telan, Giovanna Janina D.; Malijan, Frederick M.; Garcia, Jonyl L.; Fulo, Harris M.; Tongol, Bernard John V. (2011)
Studies related on the search for an effective yet less expensive catalyst and support material for fuel cells, constitute a step on the development of possible solutions to increase the efficiency of Direct Ethanol Fuel Cell while lowering its cost. Palladium nanoparticles were synthesized via oleylamine-mediated synthesis and precursor method to achieve a mean particle size of 3.78 nm ± 0.45 nm and 3.63 nm ± 0.59 nm, respectively as revealed by transmission electron microscopy (TEM). Polv(3,4-ethylenedioxythiophene) doped with poly(styrene sulfonate) (PEDOT-PSS) was prepared by a simple chemical synthesis procedure and was used as a supporting matrix for the Pd nanoparticles (PdNPs). Two different methods to remove the capping agent during the synthesis of metal nanocatalysts were studied, i.e. acetic acid washing and thermal annealing. It was found out that both thermal annealing and acectic acid washing were effective in removing the capping agent, oleylamine. The study was successful in developing an electrode based on PEDOT-PSS supported Pd nanoparticles which gave a current density of 0.90 mA/cmr^2 for ethanol oxidation in alkaline medium, which is relatively lower compared to the activity of PdNPs-CNTs (carbon nanotubes)/Naûon GCE (glassy carbon electrode) reported in the literature. The prepared electrode showed electrochemical stability even up to 50 oxidation cycles. This study is an effort pointing towards the development and possible commercialization of non-platinum based fuel cell anode dispersed on a conductive polymer matrix
Keywords: Fuel cells; Nanoparticles